GIANT NASOPHARYNGEAL CARCINOMA - A CASE REPORT DYNAMIC ANATOMICAL MODELS IN SKULL BASE AND INTRACRANIAL SPACE INVASION - Dana Turliuc; Daniela Trandafir; Andrei Cucu; Nicolae Dobrin; Gabriela Dumitrescu; Anca Sava; Ana-Maria Dumitrescu; Claudia Florida Costea (Romanian Society of Oral Rehabilitation, 2016)
Nasopharyngeal carcinoma is a head and neck cancer with a specific etiology, pathogenesis, anatomical and clinical pathology in comparison to malignancies in this region. We present the case of a patient with giant nasopharyngeal carcinoma with the invasion of the all three cerebral fossa and will try to find a few anatomical models of skull base and intracranial space invasion that are important for clinical diagnosis and imaging and in the treatment of this malignancy